Implikasi Hukum Islam terhadap Kebijakan Kewarganegaraan Ganda di Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Fatimah Azhari; Aqila Najma Nurfaizah; Kenanta Khansa Ulinnuha (International Forum of Researchers and Lecturers, 2025)
The dual citizenship policy in Indonesia is a complex issue within national law and has various implications, including from the perspective of Islamic law. Islamic law does not explicitly regulate the concept of citizenship in the modern sense but has principles that can be used to analyze this policy, such as al-wala’ (loyalty), mu’ahadah (agreements), and maqasid al-shariah (the objectives of Islamic law). This study employs a normative juridical method with a conceptual and comparative legal approach to understand how Islamic law can contribute to assessing Indonesia's dual citizenship policy. The findings indicate that although Islamic law does not explicitly prohibit dual citizenship, certain principles must be considered, such as loyalty to the state and justice in legal relations. Therefore, the implementation of the dual citizenship policy in Indonesia should take into account aspects of Islamic law to align with the national legal identity based on Pancasila and the values of justice.